ORGANIZATIONAL SUPPORT FOR REPRESENTATIVE BODY’S ACTIVITY OF LOCAL SELF-GOVERNMENT - Kovaliova O.M. (Pressing Problems of Public Administration, 2015)
In this article outlined basic principles and features of organizational support for localauthorities and their representative bodies, analyzed regulatory framework of origin and developmentof local government and suggestions are proved in relation to improve functions and tasks of localgovernments’ representative bodies in organization of local government activity after principles ofdecentralization.